. Investigating the efficacy of an interactive warning for use in labeling strategies used by us pharmacies - Lee J; Ladoni M; Richardson J; Sundar RP; Bix L (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: United States pharmacies repackage medications into multi-dose vials, enabling customized dosing for prescription drugs. Investment in infrastructure has made this the predominant approach to packaging for US prescriptions. Although recent changes to labeling now discourage the use of auxiliary labels (small stickers highlighting information germane to the safe and effective use), they are still allowed by USP<17>, provided their use comes from an evidence-based perspective. Objectives: Evaluate how 'interactive,' placements of auxiliary labels (placement requiring physical manipulation of the warning to accomplish a task (e.g. opening)) garner attention as compared to those placed vertically or horizontally. Methods: Ninety-six participants were eye tracked while opening three prescription vials (each with an auxiliary warning label with a different placement: vertical, horizontal and interactive). Recall and recognition were tested subsequently. Linear mixed models were used to analyze the continuous variables while the binary response variables were analyzed using generalized linear mixed models. The effect of auxiliary labels was fitted as a fixed effect and the subject-to-subject variation was considered as a random effect in the model. Participants' age, health literacy and sex were added to the models if their effect was statistically significant at alpha=0.05. Results: The placement of the warnings significantly impacted the time spent viewing the information they contained at alpha=0.05; people spent significantly longer on interactive placements (0.96; SD 0.13 seconds) than either, horizontal placements (0.27; SD 0.037 seconds) or those placed vertically (0.18 seconds; SD 0.035). Participants were equally as likely to see information presented in an interactive placement (90%; SD 3.8) or horizontal placement (78%; SD 05.5) but less likely to view warnings placed vertically (60%; SD 6.9). Free recall responses also supported the use of interactive placement (62%; SD 6.8 recall) as compared to horizontal placements which were 29%; SD 3.0 and 20%; SD 6.0 for vertical placements. Conclusions: Data provides evidence which suggests that interactive and horizontal placements out-perform auxiliary labels placed vertically on prescription vials with regard to garnering patient attention.